A 32-year-old male with pain and discomfort during biting (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This article has no abstract. The first 100 words appear below:A 32-year-old male patient reported to the Department of Conservative Dentistry and Endodontics, Military Dental Center, Dhaka with the complaints of mild to moderate pain and discomfort during eating in his upper left posterior region. His medical history was non-contributory. On extra oral examination, no abnormality was detected. On intraoral examination, clinically there was a dislodged restoration involving the upper left first molar tooth. On vitality test, the offending tooth showed no response to heat or cold. On percussion, ten-derness and dull percussion note were present. There was no mobility of the associated tooth.